Synthesis and characterization of Cu/Ni-zeolites -A for the direct conversion of methane to liquid hydrocarbon - Donny, Gasah (2008)
The direct conversion of methane to liquid hydrocarbon has not yet been successfully implemented in an economical process. Bimetallic zeolites showed reasonable activities for the formation of higher hydrocarbons from methane. The purpose of the present study is to modify zeolite with combine metal, copper and nickel for methane conversion into liquid hydrocarbon C. The catalysts are characterized for their physicochemical properties using the Fourier Transmitter IR Analysis (FTIR), Thermogravimetric Analysis (TGA), and X-ray Diffraction (XRD). The characterization result reveals that IR spectra indicating the presence of similar structural units and formation of identical chemical moieties of the modified zeolite samples. From XRD analysis, it is found that the synthesized modified zeolite posses a high crystallinite structure and small particle size, around 3.7 Å. TGA find that the modified zeolite catalyst is suitable for reaction in the temperature range 2000C to 70005+C due to its high thermal stability. Methane conversion to liquid hydrocarbon is predicted to increase due to loading of bi-metal Copper and Nickel. This research suggest that further studies on the catalytic performance of bi-metal for direct conversion of methane to liquid hydrocarbon should be done to make this research more complete. -Author